Modelling of neutral to earth voltage (NTEV) using RLC grounding system and current injection method / Mohd Abdul Talib Mat Yusoh, Ahmad Farid Abidin and Zuhaila Mat Yasin - Mat Yusoh, Mohd Abdul Talib; Abidin, Ahmad Farid; Mat Yasin, Zuhaila (UiTM Press, 2017)
Neutral to Earth Voltage (NTEV) rise on the commercial building can be categorized as one of the power quality (PQ) problems due to abnormal load, nonlinear load, poor grounding, and improper wiring. This paper presents the modelling of NTEV on the commercial building considering the magnitude and patterns of waveform using RLC circuit models and current injection method. The current injection and RLC circuit model are represented as a load distribution board and grounding electrode system on the commercial building respectively. Pearson correlation coefficient is utilized in order to validate the rate of accuracy on simulation model. According to the simulation, RLC grounding system produces the results which highly correlated as compare to the actual measurement.